Wpływ globalizacji na rozwój gospodarek narodowych - Ładysz, Jerzy (Influence of globalization on the development of national economies, 2006)
On the basis of rich literature of the subject in the article the author carried out the analysis of the most important impact of globalization, taking place in the economic sphere, on the development of national economies. Conclusions of the research were applied also to the Polish economy. Accession of Poland to the structures of the European Union should facilitate the adaptation of national market to global processes
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 307-313